Silicon carbide radiation detector for harsh environments - Metzger, S.; Henschel, H.; Kohn, O.; Lennartz, W. (2001 6th European Conference on Radiation and Its Effects on Components and Systems, 2001)
We used commercial off the shelf (COTS) silicon carbide (SiC) ultraviolet photodiodes for measuring gamma dose rates at high temperature. We tested them with Co-60 gamma dose rates between 0.03 mGy(Air)/s and 3 Gy(Air)/s. The diodes show excellent sensitivity, high signal to noise ratio, and good linearity. They had been operated at temperatures up to 200/spl deg/C with negligible changes of the dark and the radiation induced current. Gamma irradiation up to a total dose of 1080 kGy(Air), 32 MeV proton irradiations up to a fluence of 8.5 /spl times/ 10/sup 12/ cm/sup -2/, and 14 MeV neutron irradiations up to 4.1 /spl times/ 10/sup 12/ cm/sup -2/ demonstrate their radiation hardness. These results and the ability to measure the proton as well as the neutron dose rate after a calibration with Co-60 gammas show that COTS SiC diodes can be used as radiation detectors in harsh environments.